How do you see your role as a follower? A quantitative exploration of followers’ role orientation - Gesang, Elena (Frontiers in Psychology, 2022)
How people see and define their role in different social settings has been of interest in psychological science for several decades. However, followers’ role orientations, followers’ beliefs about their role in the workplace, and how they execute their role, have mostly been omitted in research so far. Nevertheless, followers’ role orientations are important as they can affect (work-related) behavior. Therefore, this study quantitatively investigates the structure, heterogeneity, and consistency of followers’ role orientations as well as the role orientations’ link to work-related traits and behaviors. For this purpose, content and statistical analysis of an Implicit-Followership-Theory Scale and latent profile analyses were conducted with data from two points in time via a sample of German employees (t1: n = 211, t2: n = 69). The results indicate that a passive/active work attitude (Enthusiasm) plays the most prominent part in differences in followers’ role orientation, followed by a positive/negative work ethic (Industry), and cooperativeness towards the leader (Good Citizen). Moreover, followers can be differentiated according to their role orientations into three distinct types: The Anti-Prototype, the Moderate Anti-Prototype, and the Moderate Prototype. Followers of the Moderate Prototype have the highest values in work-related traits and behaviors like conscientiousness and personal initiative. Followers’ profile affiliation is stable for three-quarters of the sample over four to six weeks. Overall, these findings point to role orientation being a (performance-related) follower characteristic, making role orientations relevant for application processes, especially for positions with frequent leader-follower interactions. Lastly, results show a current conceptual inaccuracy. They indicate the need to differentiate more rigorously between role orientations and Implicit Followership Theories, although currently both are often used synonymously. Therefore, recommendations for alterations to the used Implicit Followership Theory scale for capturing followers’ role orientations are given, including the elimination of items with situational character and changes in wording and factor structure.